2021
DOI: 10.1590/0001-3765202120201772
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenotoxicity and protective effect of piperine and capsaicin on meristematic cells of Allium cepa L.

Abstract: Piperine and capsaicin are important molecules with biological and pharmacological activities. This study aimed to evaluate the cytogenotoxic and protective effect of piperine and capsaicin on Allium cepa cells. A. cepa roots were exposed to negative (2% Dimethylsulfoxide) and positive (Methylmethanesulfonate, MMS, 10 µg/ mL) controls, and four concentrations (25-200 µM) of piperine or capsaicin (alone) or associated before, simultaneously or after with the MMS. Only the lowest concentration of piperine (25 µM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Our analyzes indicated that piperine decreases cell viability upon application of the treatment, and it was even pointed out that the main biological effects of piperine in vitro occur at specific doses (75-200 µM) and incubation time between 24 and 48 hours [15]. This cytotoxicity effect is described as piperine promoting inhibition of NADH-oxidoreductase, an enzyme that stimulates cell activity and proliferation, as well as disruption of mitochondrial membrane permeability [16].…”
Section: Discussionmentioning
confidence: 74%
“…Our analyzes indicated that piperine decreases cell viability upon application of the treatment, and it was even pointed out that the main biological effects of piperine in vitro occur at specific doses (75-200 µM) and incubation time between 24 and 48 hours [15]. This cytotoxicity effect is described as piperine promoting inhibition of NADH-oxidoreductase, an enzyme that stimulates cell activity and proliferation, as well as disruption of mitochondrial membrane permeability [16].…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, Gömürgen (2005) also found that the mitotic index decreases with an increase in the concentration of potassium metabisulfite in onion apical meristem. Dias et al (2021) demonstrated cytotoxic effects of piperine, as a significant decrease in the mitotic index was observed. The root growth is controlled by a cell division in the active meristem zone, as well as by cell elongation, whereby these two processes represent independent events (Shishkova et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…Our findings are in concordance to those from Gömürgen (2005), who observed a numerous chromosomal abnormalities in A. cepa meristem cells, such as residual chromosomes, anaphase and telophase bridges and multipolar anaphase cells, of which the most common were cells with anaphase bridges. One study demonstrated cyto/genotoxic effects of piperine due to significant increase in the chromosomal changes, pointing out at the same time that the lowest piperine concentration was not genotoxic and showed a protective effect, indicating its slight antimutagenic potential that apparently depends on the piperine concentration itself (Dias et al, 2021). Based on modern studies on animal cells, piperine has been found to have immunomodulating, antioxidant, anticancer and anti-inflammatory properties (Meghwal & Goswami, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Os estudos incluídos foram publicados em português (Frota et al, 2019), inglês (Pereira et al, 2017;Wandscheer et al, 2017;Montalvão et al, 2019;Khan;Anas;Malik, 2019;Almeida et al, 2020;Dias et al, 2021;Frâncica et al, 2021;Ferreira et al, 2022) e espanhol (López-Rojas; Becerra-Gutiérrez; Díaz-Vélez, 2019). Dois artigos (Pereira et al, 2017;Khan;Anas;Malik, 2019) apresentaram nível I de evidências e oito artigos (Wandscheer et al, 2017;Frota et al, 2019;López-Rojas;Becerra-Gutiérrez;Díaz-Vélez, 2019;Montalvão et al, 2019;Almeida et al, 2020;Dias et al, 2021;Frâncica et al, 2021;Ferreira et al, 2022) apresentaram nível II.…”
Section: Resultados E Discusãounclassified